Fly ash scale and preparation method and application thereof
By melting fly ash with other substances at high temperature and forming them quickly, fly ash scales are prepared, which solves the problem of low utilization value of fly ash, and the scales are achieved with acid and alkali resistance, fire resistance and excellent dielectric properties. The adhesion and wear resistance are significantly improved in coatings.
Patent Information
- Application Number
- CN202411855195.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
AI Technical Summary
In the prior art, fly ash is mainly used as filler, and its components are not fully utilized, resulting in low added value. How to improve the utilization value of fly ash has become an urgent problem that researchers need to solve.
Fly ash scales were prepared by mixing fly ash, potassium carbonate, sodium feldspar and oxide, melting at high temperature, and then homogenizing, and then quenching to form. This method stimulates the activity of metal oxide components in fly ash, forms glass microbeads, and improves the refractory properties of the scales through high-temperature melting process.
The prepared fly ash scale has a translucent gold-green sheet-like structure, which is resistant to acid and alkali corrosion, has excellent refractory properties, and increases the surface area through negative pressure quench molding, creating a shielding effect. When used in coatings, it significantly improves the adhesion and wear resistance of the coating, and has excellent dielectric properties and high and low temperature resistance.
Smart Images

Figure BDA0005191616840000051 
Figure BDA0005191616840000061 
Figure BDA0005191616840000062
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solid waste materials, and in particular to a fly ash flake and a preparation method and application thereof. Background Art
[0002] Fly ash is the fine ash collected from the flue gas after coal combustion, and is the main solid waste discharged from coal-fired power plants. Fly ash is usually gray or gray-black. If a large amount of fly ash is not treated, it will produce dust and pollute the atmosphere; if it is discharged into the water, it will also cause river pollution. In addition, some chemical substances contained in fly ash will affect the human body and organisms, causing irreparable damage. Based on this, researchers began to explore the resource utilization of fly ash. It is common to use fly ash in building materials, use fly ash as an admixture for concrete, prepare cement, mortar, etc., which can significantly reduce the raw material cost of the enterprise. The above-mentioned utilization method only uses fly ash as a filler, and does not utilize the various components in it, and has low added value. Therefore, how to improve the utilization value of fly ash and make full use of fly ash has become a problem that researchers urgently need to solve. Summary of the invention
[0003] The purpose of the present invention is to overcome the defects in the prior art and provide a fly ash flake and a preparation method and application thereof.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a method for preparing fly ash flakes, comprising the following steps:
[0006] (1) mixing fly ash, potassium carbonate, albite and oxide to obtain a mixture;
[0007] (2) melting the mixture at high temperature and then homogenizing it to obtain a molten liquid;
[0008] (3) The molten liquid is rapidly cooled and formed to obtain the fly ash flakes.
[0009] Preferably, the oxide in step (1) comprises tin oxide and cerium oxide,
[0010] The mass ratio of tin oxide to cerium oxide is 0.5-0.8:1.
[0011] Preferably, in step (1), the mass ratio of fly ash, potassium carbonate, albite and oxide is 100:3-5:6-7:0.5-1.
[0012] Preferably, the ball-to-material ratio in step (1) is 10-12:1, the mass of the grinding aid is 3-5% of the weight of the fly ash, and the grinding aid comprises stearic acid and / or polyvinyl alcohol;
[0013] The mixing speed is 70-80 rpm and the mixing time is 8-15 hours.
[0014] Preferably, the pre-melting temperature of the high temperature melting in step (2) is 1400-1500° C., and the pre-melting time is 1-2 h.
[0015] Preferably, the clarification temperature of the high temperature melting in step (2) is 1600-1650°C;
[0016] The heating rate from the pre-melting temperature of the high temperature melt to the clarifying temperature of the high temperature melt is 10-15°C / min;
[0017] The holding time to reach the high temperature melting and clarification temperature is 4 to 5 hours.
[0018] Preferably, the homogenization temperature in step (2) is 1350-1400° C., the rotation speed is 10-20 rpm, and the time is 10-15 min.
[0019] Preferably, the negative pressure value of the rapid cooling molding in step (3) is -0.05 to -0.1 MPa, the rapid cooling temperature is 400 to 500°C, and the rapid cooling time is 30 to 60 seconds.
[0020] The invention also provides fly ash flakes prepared by the preparation method of the fly ash flakes.
[0021] The invention also provides application of the fly ash flakes in coatings.
[0022] The present invention provides a method for preparing fly ash flakes, comprising the following steps: mixing fly ash, potassium carbonate, sodium feldspar and oxides to obtain a mixture; melting the mixture at high temperature and then homogenizing to obtain a molten liquid; and rapidly cooling the molten liquid to obtain the fly ash flakes. The present invention determines the raw materials of the flakes by compatibility, stirs and mixes them by ball milling, fully stimulates the activity of the metal oxide components in the fly ash, and forms glass microspheres; and obtains a fish-scale-like, translucent golden green flaky structural material by subsequent high-temperature melting, homogenization and rapid cooling. In the present invention, the fly ash contains a large amount of acidic oxides and alkaline oxides, which form aluminosilicate minerals such as chalcedony under high temperature conditions and are resistant to acid and alkali corrosion; and after a high-temperature melting process, the flakes have excellent fire resistance. The added oxides are used to clarify the molten liquid, discharge bubbles and improve the quality; mechanical homogenization improves the uniformity of the molten liquid and improves the homogenization effect. The flaky fly ash is finally obtained by negative pressure rapid cooling molding, which increases the surface area of the fly ash and produces a shielding effect. The present invention uses fly ash as the main raw material, which contains 8-10% magnetic iron components. The scales formed after high-temperature melting, heat preservation, homogenization and clarification have strong sound and wave absorption effects. Adding it to paint coatings improves the adhesion between the coating and the substrate.
[0023] The method provided by the invention is simple and can produce a large amount of flake fly ash. Moreover, due to the stable high-temperature and low-temperature resistance, as well as the excellent dielectric and chemical corrosion resistance, the flake fly ash has great development prospects. DETAILED DESCRIPTION
[0024] The present invention provides a method for preparing fly ash flakes, comprising the following steps:
[0025] (1) mixing fly ash, potassium carbonate, albite and oxide to obtain a mixture;
[0026] (2) melting the mixture at high temperature and then homogenizing it to obtain a molten liquid;
[0027] (3) The molten liquid is rapidly cooled and formed to obtain the fly ash flakes.
[0028] In the present invention, the oxide in step (1) comprises tin oxide and cerium oxide.
[0029] In the present invention, the mass ratio of tin oxide to cerium oxide is preferably 0.5 to 0.8:1, more preferably 0.55 to 0.75:1, and even more preferably 0.6 to 0.7:1.
[0030] In the present invention, the mass ratio of fly ash, potassium carbonate, sodium feldspar and oxide in step (1) is preferably 100:3-5:6-7:0.5-1, further preferably 100:3.5-4.5:6.2-6.8:0.6-0.9, and more preferably 100:3.8-4.2:6.4-6.6:0.7-0.8.
[0031] In the present invention, the ball-to-material ratio mixed in step (1) is preferably 10-12:1, more preferably 10.5-11.5:1, and more preferably 10.8-11.2:1; the mass of the grinding aid is preferably 3-5% of the weight of the fly ash, more preferably 3.5-4.5%, and more preferably 3.8-4.2%; the grinding aid comprises stearic acid and / or polyvinyl alcohol.
[0032] In the present invention, the mixing speed is preferably 70 to 80 rpm, more preferably 72 to 78 rpm, and more preferably 74 to 76 rpm; the mixing time is preferably 8 to 15 h, more preferably 9 to 14 h, and more preferably 10 to 13 h.
[0033] In the present invention, the pre-melting temperature of the high-temperature melting in step (2) is preferably 1400-1500°C, more preferably 1420-1480°C, and more preferably 1440-1460°C; the pre-melting time is preferably 1-2h, more preferably 1.2-1.8h, and more preferably 1.4-1.6h.
[0034] In the present invention, the clarification temperature of the high temperature melting in step (2) is preferably 1600-1650°C, more preferably 1610-1640°C, and even more preferably 1620-1630°C.
[0035] In the present invention, the heating rate from the high temperature melting pre-melting temperature to the high temperature melting clarification temperature is preferably 10-15°C / min, more preferably 11-14°C / min, and even more preferably 12-13°C / min.
[0036] In the present invention, the holding time to reach the high-temperature melting and clarifying temperature is preferably 4 to 5 hours, more preferably 4.2 to 4.8 hours, and even more preferably 4.4 to 4.6 hours.
[0037] In the present invention, after the high-temperature melting clarification process is completed, the temperature is lowered to the homogenization temperature, and the cooling rate is preferably 5 to 10°C / min, more preferably 6 to 9°C / min, and more preferably 7 to 8°C / min.
[0038] In the present invention, the homogenization temperature in step (2) is preferably 1350-1400°C, more preferably 1360-1390°C, and more preferably 1370-1380°C; the rotation speed is preferably 10-20 rpm, more preferably 12-18 rpm, and more preferably 14-16 rpm; the time is preferably 10-15 min, more preferably 11-14 min, and more preferably 12-13 min.
[0039] In the present invention, the negative pressure value of the quenching molding in step (3) is preferably -0.05 to -0.1 MPa, more preferably -0.06 to -0.09 MPa, and more preferably -0.07 to -0.08 MPa; the quenching temperature is preferably 400 to 500°C, more preferably 420 to 480°C, and more preferably 440 to 460°C; the quenching time is preferably 30 to 60s, more preferably 35 to 55s, and more preferably 40 to 50s.
[0040] The invention also provides fly ash flakes prepared by the preparation method of the fly ash flakes.
[0041] The present invention also provides the use of the fly ash flakes in coatings
[0042] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0043] Example 1
[0044] Prepare 100g fly ash, 4g potassium carbonate, 6g albite and 0.6g oxide (the mass ratio of tin oxide to cerium oxide is 0.5:1), mix the above raw materials, the ball-to-material ratio is 10:1, stearic acid is used as a grinding aid, the mass of the grinding aid is 4% of the mass of the fly ash, the rotation speed is controlled at 75rpm, the time is 10h, and a mixture is obtained.
[0045] The mixture was pre-melted at 1400°C for 2 hours, and then the temperature was raised to 1630°C at a heating rate of 12°C / min and clarified for 4 hours; then the temperature was lowered to 1400°C at a rate of 6°C / min, and the mixture was stirred at a stirring speed of 15 rpm for 10 minutes to complete homogenization and obtain a molten liquid.
[0046] The molten liquid is rapidly cooled and formed, the negative pressure value is controlled to be -0.07MPa, the temperature is 450°C, the time is 50s, the molten liquid is drained and formed, and then naturally cooled to room temperature to obtain fly ash flakes.
[0047] Example 2
[0048] Prepare 500g fly ash, 15g potassium carbonate, 35g albite and 4g oxide (the mass ratio of tin oxide to cerium oxide is 0.6:1), mix the above raw materials, the ball-to-material ratio is 12:1, polyvinyl alcohol is used as a grinding aid, the mass of the grinding aid is 3.5% of the mass of the fly ash, the rotation speed is controlled at 80rpm, the time is 14h, and a mixture is obtained.
[0049] The mixture was pre-melted at 1460°C for 1.5h, then the temperature was raised to 1650°C at a heating rate of 11°C / min and clarified for 4.6h; then the temperature was lowered to 1360°C at a rate of 7°C / min, and the mixture was stirred at 20rpm for 12min to complete homogenization and obtain a molten liquid.
[0050] The molten liquid is rapidly cooled and formed, the negative pressure value is controlled to be -0.09 MPa, the temperature is 500°C, the time is 35 seconds, the molten liquid is drained and formed, and then naturally cooled to room temperature to obtain fly ash flakes.
[0051] Example 3
[0052] Prepare 1000g fly ash, 30g potassium carbonate, 68g albite and 9g oxide (the mass ratio of tin oxide to cerium oxide is 0.8:1), mix the above raw materials, the ball-to-material ratio is 11:1, polyvinyl alcohol is used as a grinding aid, the mass of the grinding aid is 5% of the mass of the fly ash, the rotation speed is controlled at 72rpm, the time is 9h, and a mixture is obtained.
[0053] The mixture was pre-melted at 1410°C for 1 hour, and then the temperature was raised to 1620°C at a heating rate of 14°C / min and clarified for 5 hours; then the temperature was lowered to 1400°C at a rate of 10°C / min, and the mixture was stirred at a stirring speed of 10 rpm for 10 minutes to complete homogenization and obtain a molten liquid.
[0054] The molten liquid is rapidly cooled and formed, the negative pressure value is controlled to be -0.1MPa, the temperature is 420℃, the time is 55s, the molten liquid is drained and formed, and then naturally cooled to room temperature to obtain fly ash flakes.
[0055] The thickness of the fly ash flakes prepared in Examples 1 to 3 was measured, and 7 pieces of each example were randomly weighed for testing. The results are recorded in Table 1.
[0056] Table 1 Fly ash flake thickness test results
[0057]
[0058]
[0059] The fly ash flakes prepared in Examples 1 to 3 were applied to the coating for performance testing. The specific formula was as follows: 38 parts of epoxy resin, 11 parts of 650 polyamide curing agent, 1.8 parts of polydimethylsiloxane, and 3.3 parts of fly ash flakes. The slurry was ground and the fineness was controlled to 40 to 50 μm.
[0060] The comparative example is a coating system without adding fly ash flakes.
[0061] The composite coating was tested for salt spray resistance according to the national standard GB / T6461-2002, and for wear resistance according to GB / T1768-2006 "Determination of wear resistance of paints and varnishes - Rotating rubber grinding wheel method". The frequency of the dielectric test was 10 -1 and 10 5 Hz, high and low temperature shock was carried out in a high and low temperature shock test chamber, -60℃~+100℃ cycled 3 times, staying in each temperature section for 3h; the results are recorded in Table 2.
[0062] Table 2 Performance test results
[0063]
[0064]
[0065] It can be seen from Table 2 that after adding fly ash flakes, the salt spray resistance of the coating has been greatly improved; this is because after adding fly ash flakes, they are overlapped and overlapped in the coating, effectively hindering the invasion of corrosive media, and the presence of flakes can effectively increase the density, reduce the number of bubbles inside the coating, and improve the density of the coating. In the wear resistance test, the addition of flakes effectively reduced the mass loss of the coating and met the wear resistance performance index. It can be seen that the addition of fly ash flakes effectively improves the dielectric constant of the coating and has excellent resistance to high and low temperature impact.
[0066] As can be seen from the above embodiments, the present invention provides a method for preparing fly ash flakes, comprising the following steps: mixing fly ash, potassium carbonate, sodium feldspar and oxide to obtain a mixture; melting the mixture at high temperature and homogenizing to obtain a molten liquid; and rapidly cooling the molten liquid to obtain the fly ash flakes. The fly ash flakes provided by the present invention have excellent performance. When applied to coatings, the salt spray time can reach 176h, the wear resistance mass loss is as low as 496mg, and the dielectric constant is between 10 -1 Hz is 6.0, 10 5 Hz is 5.2; it cycles 3 times at -60℃~+100℃, staying in each temperature range for 3 hours, and it does not crack at low temperatures and does not deform at high temperatures. The fly ash flakes provided by the present invention have excellent performance and great development prospects.
[0067] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing fly ash flakes, characterized in that: It includes the following steps: (1) mixing fly ash, potassium carbonate, albite and oxide to obtain a mixture; (2) melting the mixture at high temperature and then homogenizing it to obtain a molten liquid; (3) The molten liquid is rapidly cooled and formed to obtain the fly ash flakes.
2. The method for preparing fly ash flakes according to claim 1, characterized in that: The oxide in step (1) comprises tin oxide and cerium oxide, The mass ratio of tin oxide to cerium oxide is 0.5-0.8:
1.
3. The method for preparing fly ash flakes according to claim 1 or 2, characterized in that: In step (1), the mass ratio of fly ash, potassium carbonate, sodium feldspar and oxide is 100:3-5:6-7:0.5-1.
4. The method for preparing fly ash flakes according to claim 3, characterized in that: The ball-to-material ratio in step (1) is 10-12:1, the mass of the grinding aid is 3-5% of the weight of the fly ash, and the grinding aid comprises stearic acid and / or polyvinyl alcohol; The mixing speed is 70-80 rpm and the mixing time is 8-15 hours.
5. The method for preparing fly ash flakes according to claim 1 or 4, characterized in that: The pre-melting temperature of the high-temperature melting in step (2) is 1400-1500° C., and the pre-melting time is 1-2 hours.
6. The method for preparing fly ash flakes according to claim 5, characterized in that: The clarification temperature of the high temperature melting in step (2) is 1600-1650°C; The heating rate from the pre-melting temperature of the high temperature melt to the clarifying temperature of the high temperature melt is 10-15°C / min; The holding time to reach the high temperature melting and clarification temperature is 4 to 5 hours.
7. The method for preparing fly ash flakes according to claim 6, characterized in that: In step (2), the homogenization temperature is 1350-1400° C., the rotation speed is 10-20 rpm, and the time is 10-15 min.
8. The method for preparing fly ash flakes according to claim 1 or 7, characterized in that: The negative pressure value of the rapid cooling molding in step (3) is -0.05 to -0.1 MPa, the rapid cooling temperature is 400 to 500° C., and the rapid cooling time is 30 to 60 seconds.
9. Fly ash flakes prepared by the method for preparing fly ash flakes according to any one of claims 1 to 8.
10. Use of the fly ash flakes according to claim 9 in coatings.